ANALISIS PERBEDAAN LANTAI KANDANG DAN DAMPAKNYA TERHADAP PERTUMBUHAN KELINCI SAPIHAN - Shirley Fredriksz; Lily Joris; Febriyanti Lamhari (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study aimed to determine the effect of utilizing different cage flooring types on the growth performance of weanling rabbits. The experiment involved 12 local weanling rabbits aged 7 to 8 weeks, comprising 6 males and 6 females, with an average initial body weight of 350 grams. Fresh water spinach (Ipomoea aquatica), chopped to a uniform length of 5 cm, was provided ad libitum as the primary feed resource. The animals were housed individually in a 12-compartment battery cage system measuring 90 × 60 × 60 cm per unit. The experimental design utilized a Completely Randomized Design (CRD) consisting of 3 treatments and 4 replications. The treatments evaluated were: P1 (slatted wooden floor), P2 (wire mesh floor), and P3 (solid wooden floor). The experimental results revealed significant differences among treatments regarding feed consumption. Specifically, the solid wooden floor treatment (P3) exhibited a distinct variation compared to the slatted wooden floor (P1) and wire mesh floor (P2) treatments. Conversely, no significant differences were observed among the treatments in terms of body weight gain and feed conversion ratio (FCR).